The effect of the antioxidant drug U-74389G on endometrial edema during ischemia reperfusion injury in rats - Tsompos, Constantinos N.; Panoulis, Constantinos P. C. (Acta Biologica Szegediensis, 2014)
The aim of this experiment was to study the effects of the antioxidant drug U-74389G on rat model, particularly in ischemia reperfusion (IR) protocol. The beneficial or other effects of that molecule were studied pathologically using endometrial edema (EE) lesions. Forty rats were used of mean weight 231.875 gr. EE lesions were evaluated 60 min after reperfusion (groups A and C) and 120 min after reperfusion (groups B and D), with administration of the drug U-74389G in groups C and D. Results were that U-74389G administration non-significantly decreased without lesions the EE scores by 0.41 [-1.00 - 0.17] (p= 0.1607). This finding was in accordance with the results of Wilcoxon signed-rank test (p= 0.5229). Reperfusion time non-significantly increased without lesions the EE scores by 0.21 [-0.38 - 0.81] (p= 0.4701), also in accordance with Wilcoxon signed-rank test (p= 0.1022). However, U-74389G administration and reperfusion time together non-significantly decreased without lesions the EE scores by 0.17 [-0.53 - 0.18] (p= 0.3383). Results of this study indicate that U-74389G administration hardly non-significantly decreases without lesions the EE within short-term time context of 2 hours.